Advances in pharmacotherapy for primary biliary cirrhosis. (April 2015) - Mousa, Hani S; Lleo, Ana; Invernizzi, Pietro; Bowlus, Christopher L; Gershwin, Merril Eric
<x xml:space="preserve">Abstract</x> Introduction: Primary biliary cirrhosis (PBC) is a chronic autoimmune liver disease mostly seen in middle-aged women characterized by progressive nonsuppurative destruction of small bile ducts resulting in intrahepatic cholestasis, parenchymal injury and ultimately end-stage liver disease. Despite major breakthroughs in our understanding of PBC, there remains only one FDA-approved agent for treatment: ursodeoxycholic acid (UDCA) to which one-third of patients are unresponsive. Areas covered: Biochemical response to treatment with UDCA is associated with excellent survival rates in PBC patients. However, there is a need for alternative treatments for nonresponders. Results from human epidemiological and genetic studies as well as preclinical studies in PBC animal models have provided a strong impetus for the development of new therapeutic agents. In this review, we discuss the recent advances in translational research in PBC focusing on promising therapeutic approaches, namely immune-based targeted therapies and agents targeting the synthesis and circulation of bile acids. Expert opinion: We are in a new era for the development of novel therapies for PBC. Data on fibrates, budesonide and obeticholic acid offer encouragement for nonresponders to UDCA.